2022
DOI: 10.21608/alexja.2022.159058.1025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bacillus subtilis, Trichoderma spp. and The Bioproduct Top Perfect on Meloidogyne incognita Infecting Pepper Plants

Abstract: Root-knot nematodes are considered one of the severe plant pathogens that can be managed effectively with chemical nematicides in spite of their hazards to humans and the environment. Our work focus on the efficacy of Bacillus subtilis, Trichoderma spp. culture filtrates, the bioproduct Top perfect and the nematicide Vydate ® L 24% for controlling Meloidogyne incognita infecting pepper plants cv. Balady. Under laboratory and greenhouse conditions, treatments with 0.025 and 0.05 μl of Vydate ® L 24%/ml distille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…On the other hand, bacteria of the Bacillus genus are well-known plant growth promoters and are also effective in biological control of different pests. Reports exist of suppression of Meloidogyne populations by Bacillus subtilis in chili (Capsicum annuum) (Mokbel et al, 2022;Soto Deza et al, 2012) and tomato (Basyony and Abo-Zaid, 2018), while BMH and INV strains of a Bacillus species related to Bacillus velezensis, reduced the number of galls and eggs of M. incognita by more than 90% in tomato (Cruz-Magalhães et al, 2022). Tian et al, (2022) reported that B. velezensis Bv25 reduced galls caused by M. incognita on cucumber roots by 73.8%, through root colonization and production of volatile compounds.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, bacteria of the Bacillus genus are well-known plant growth promoters and are also effective in biological control of different pests. Reports exist of suppression of Meloidogyne populations by Bacillus subtilis in chili (Capsicum annuum) (Mokbel et al, 2022;Soto Deza et al, 2012) and tomato (Basyony and Abo-Zaid, 2018), while BMH and INV strains of a Bacillus species related to Bacillus velezensis, reduced the number of galls and eggs of M. incognita by more than 90% in tomato (Cruz-Magalhães et al, 2022). Tian et al, (2022) reported that B. velezensis Bv25 reduced galls caused by M. incognita on cucumber roots by 73.8%, through root colonization and production of volatile compounds.…”
Section: Introductionmentioning
confidence: 99%